Adolescent tobacco menace: Attitudes, norms, and parental influence - Preeti Sharma; Vijay Wadhwan; Pooja Aggarwal; Neeraj Sharma (Wolters Kluwer Medknow Publications, 2017)
Background: Adolescence is a very delicate and vulnerable age when children are exposed to the harmful and damaging culture of the society. Tobacco habits are increasingly becoming an annoying menace to the Indian society since the past few years. The teenage group is fast catching up the tobacco habits because of its easy availability in the local Indian markets. Thus, this study was envisaged to analyze the factors responsible for this adverse habit and to obtain an overview of the trends in tobacco habits in young children of North India. Methods: Eight hundred and sixteen schoolchildren in the age group of 14-19 years of different schools of Meerut city were instructed to fill the prepared questionnaires. Results were formulated and statistical analysis was done. Results: Chi-square analysis revealed significant difference between tobacco users and nonusers. Smokeless habit was more prevalent among adolescent boys. Peer pressure was the most cited reason for initiating the tobacco habit while parental influence helped the most in abstaining from this adverse addiction. Conclusion: Despite the existence of anti-tobacco regulations in India, tobacco dependence in adolescents raises an alarm for the Indian community and stringent steps are required to remove this menace.